Mobility program impact on the internationalization of higher education at The Faculty of Social and Psychological Education of Pavlo Tychyna Uman State Pedagogical University - Kravchenko, Oksana; Koliada, Nataliia; Safin, Aleksandr; Boiko, Olha (Wpływ programu mobilności na internacjonalizację szkolnictwa wyższego na Wydziale Edukacji Społecznej i Psychologicznej Państwowego Uniwersytetu Pedagogicznego im. Pawła Tyczyny w Umaniu, 2023)
The article deals with the issues of international academic mobility of students, teaching and research related to internationalization of higher education at the Faculty of Social and Psychological Education of Pavlo Tychyna Uman State Pedagogical University. Given the ever-increasing requirements towards the quality of higher education, Ukrainian higher education institutions (HEI) faced the problem of the need to increase competitiveness on the world market. All this indicates that international university cooperation constitutes an integral part of the existence and development of Ukrainian higher education institutions. International cooperation, academic mobility of students, participation in international educational programs and projects are the priority in the development of today’s education. Thanks to inter-university partnerships, young people study together with their peers from different countries of the world, increase their understanding of intercultural issues, and adapt to life and work in the global space.
Zeszyty Naukowe Collegium Witelona, nr 46(1)/2023, s. 69-80
Keywords: university; internationalization; higher education dynamics; mobility; providers of educational services; strategy; działalność międzynarodowa; praca socjalna; psychologia praktyczna; szkolnictwo wyższe; instytucje edukacyjne; młodzież studencka; współpraca międzynarodowa; przestrzeń inkluzywna; działalność projektowa